2019
DOI: 10.1371/journal.pone.0214329
|View full text |Cite|
|
Sign up to set email alerts
|

Analgesic use among the Brazilian population: Results from the National Survey on Access, Use and Promotion of Rational Use of Medicines (PNAUM)

Abstract: PurposeTo estimate the prevalence of use of analgesics in Brazil; and to characterize this use, according to sociodemographic and health-related characteristics.MethodsA cross-sectional population-based study (National Survey on Access, Use and Promotion of Rational Use of Medicines, PNAUM) was conducted between September 2013 and February 2014. A total of 41,433 people of all ages in Brazilian urban households were interviewed. Occasional use (within the last 15 days) and continuous use of non-opioid analgesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
0
20
0
5
Order By: Relevance
“…The sample was calculated using the Leslie and Kish formula for a single proportion. The best estimate of the proportion of elderly patients using analgesics (32.4%)[ 21 ] was used to derive the sample size of 337 at a precision of 5%.…”
Section: Ethodsmentioning
confidence: 99%
“…The sample was calculated using the Leslie and Kish formula for a single proportion. The best estimate of the proportion of elderly patients using analgesics (32.4%)[ 21 ] was used to derive the sample size of 337 at a precision of 5%.…”
Section: Ethodsmentioning
confidence: 99%
“…To improve the rationality of antibiotic usage in prescriptions and dispensing of antibiotics, the World Health Organization (WHO) established the International Network for Rational Use of Drugs (INRUD) through the design, evaluation and promotion of effective strategies in 1989 [3]. In addition, many countries have implemented a policy of rational antibiotic usage to standardize prescribing behavior and enhance the integrity of medical units [4,5,6,7,8,9,10]. However, the dilemma of irrational antibiotic usage remains unresolved in the healthcare industry worldwide, especially in developing countries [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…37 A crosssectional population-based study performed in Brazil, where metamizole is sold over the counter, analyzed 41 433 individuals and revealed that metamizole is the most used self-medication. 38,39 Figure 1 gives an overview of the legal status of metamizole worldwide according to the literature. 6,[28][29][30][31] Furthermore, it must be taken into account that metamizole is widely used by immigrants, even in countries where the substance is banned.…”
mentioning
confidence: 99%
“…In countries where metamizole is sold over the counter, the drug is used as a common self‐medication and is the most taken analgesic agent in patients with chronic pain . A cross‐sectional population‐based study performed in Brazil, where metamizole is sold over the counter, analyzed 41 433 individuals and revealed that metamizole is the most used self‐medication . Figure gives an overview of the legal status of metamizole worldwide according to the literature …”
mentioning
confidence: 99%